Color Converting Film With Quantum-Dots for the Liquid Crystal Displays Based on Inkjet Printing - Bing-Le Huang; Tai-Liang Guo; Sheng Xu; Yun Ye; En-Guo Chen; Zhi-Xian Lin (IEEE Photonics Journal, 2019)
The color converting film (CCF) is first fabricated by the inkjet printing technology with the drop-on-demand advantage in the paper, the volume ratio of the red quantum-dots (QDs) over green QDs is 1:12.9 at balanced intensity, and each subpixel of the CCF is sprayed with five droplets with each volume of 48 pL. The CCF has been equipped in the corresponding liquid crystal display (LCD) module. In theory, the optical efficiency of the CCF mainly depends on the quantum yield of QDs, therefore, and the total optical efficiency can improve by 2.4 times. The LCD module sample has been tested to verify the performance. Experimental results show that the color gamut reaches 131.4% NTSC in CIE 1931, the total optical efficiency is 20%. Comparing with the wide color gamut backlight module with QDEF, the color gamut improves by 16.4% NTSC, the total optical efficiency improves by 2.1 times, and the average color crosstalk ratio decreases by 4.21% under the condition that the misaligned size is larger than the width of the black matrix. Our method provides theoretical guidance to realize high-performance LCDs.